Inclusive Growth: A Poverty Approach - Soleh, Ahmad; Sukiyono, Ketut; Nurazi, Ridwan (Technium Business and Management, 2022)
The concept of inclusive growth (IG) was present in the last decade and together with the concept of pro-poor growth. Characteristic of the concept of inclusive growth is the active participation and contribution of the community in the development process. Several approaches have been developed in measuring inclusive growth. This study aims to measure inclusive growth using the provincial poverty approach (IGp) on the island of Sumatra for the period 2001-2016. The method of approach used in this study is descriptive analysis. The technique of collecting data uses library research. Poverty-Equivalent Growth Rate (PEGR) was developed in the measurement of inclusive growth. The results showed that the provincial economic growth on the island of Sumatra in general was not inclusive. The inclusive growth coefficient (IGp) in most provinces is positive but lower than the economic growth coefficient (Gg). The average IGp coefficient of Sumatra island is 0.032 lower than the Gg coefficient of 0.049. The performance of economic growth determines the value of the coefficient of economic growth and the coefficient of inclusive growth. However, the high economic growth of a region does not guarantee the realization of an inclusive growth. Quality economic growth is not only based on high economic growth achievements but the ability of economic growth to reduce poverty. Policies related to improving development and poverty alleviation programs need to be carried out in an integrated and synergic. manner between ministries or institutions from national to regional levels